(390) Lectures on Queuing Theory محاضرات حول نظرية المصفوفة - Saaty, T. L. (معهد التخطيط القومى, 2024)
This study explores the theory of queues (waiting lines) within a structural framework, emphasizing mathematical models and solution methods with applications in various fields such as telephone traffic, inventory management, machine repairs, and airport operations. Chapter 1 introduces the structure of queues descriptively, while Chapter 2 provides technical insights for interested readers. Chapters 3 to 5 focus on probability theory and mathematical analysis for solving queuing problems, with Chapters 4 and 5 specializing in Poisson queues. Chapters 6 to 13 expand on the structure, followed by applications in Chapter 14. Chapter 15 addresses renewal theory, ending with a comprehensive bibliography. Queue optimization is introduced by balancing investments in resources with profit maximization, helping reduce customer loss and improve